Моделирование свойств материалов биомеханических систем: модели, подходы, численный эксперимент - Веретельник, Юрий Викторович (НТУ "ХПИ", 2005)
This article is devoted to some mechanical research aspects of vertebra body stressedly-deformed state. The specified models are built vertebra bodies, which can be used for further researches. The quality and quantitative influencing analysis of the elasticity modulus and anisotropy is conducted on the vertebra behaviour
Keywords: исследования костей; проектирование эндопротеза; кортикальная кость; трабекулярная кость; исследования позвоночного столба